Prevalence of osteoporosis in patients with liver cirrhosis. - Ahmed , Shaista; Iqbal , Sadia; Siddiqui, Afshan; Hassan, Mujtaba; Ahmed , Aisha; Altaf, Anila (International Journal of Endorsing Health Science Research, 2022)
Background: In the recent past, numerous researchers have analyzed dissimilar aspects of osteoporosis in liver cirrhosis, we still have deficient indigenous literature. The present study aims to determine the frequency of osteoporosis with liver cirrhosis. Methodology: A prospective observational study was carried out at the Tertiary referral center of Karachi. Osteoporosis of liver cirrhosis patients was established as specified by WHO using dual-energy X-ray absorptiometry (DXA) on the L1-L4 spine and having spine bone mineral density (BMD) expressed as T score <-2.5. Short history related to the duration of the disease was recorded. The patient's BMD expressed as a T score was measured using DXA on the spine. Results: Among patients who had presented with a duration of cirrhosis of 5 years or less, 20(6.75%) had osteoporosis, whereas 62(20.9%) had it with a duration > 5 years (p=0.000). As far as outcome of the patients is concerned 52(17.5%) and 30(10.1%) patients had osteoporosis with BMI < 25 kg/m2 and > 25 kg/m2 respectively (p=0.590). When layered according to the Childs Class, among patients with Class A, B, and C, 0.33%, 3.37%, and 23.9% of patients had osteoporosis (p=0.050). Conclusion: In conclusion, the prevalence of osteoporosis in patients with cirrhosis was found to be 27.7%. Furthermore, patients with a longer duration of disease, low BMI, and with child class C are at greater threat of the occurrence of osteoporosis and require early detection and prompt treatment.